Numerical simulation for the dynamics of the nanoparticles driven by Poisson white noise - Bondar, Olena (Видавництво Львівської політехніки, 2013)
In this work we numerically simulated the dynamics of the nanoparticles driven by Poisson white noise in the case of a quadratic potential. In the equation, which described the motion of the nanoparticles, the components of Poisson white noise are represented as a random variables distributed according to the Poisson law. Take it into account, we obtained the mathematical algorithm, based on which, we got the probability density distribution of the nanoparticles that are located in the potential well. The results of numerical simulation are presented on the graph, where they are compared with the previously obtained analytical solution.
Keywords: Poisson white noise; probability density distribution; potential well